The relationship between malocclusion, bruxism, clicking sound and hypertonus of masseter muscle in austism spectrum disorders - Lisda Damayanti; Calvin Atherton; Erna Kurnikasari; Inne S. Sasmita (DiscoverSys Inc., 2022)
Objective: To determine the relationship between malocclusion, bruxism, clicking sound, and hypertonus masseter muscle in autism spectrum disorders. Material and Methods: The study was conducted on 20 children of autism spectrum disorder at Prananda Autism Education Institute in Bandung. Examination was carried out on the sample to determine the type of malocclusion, the presence of bruxism, clicking sound, and hypertonus of masseter muscle. Results: The data obtained was processed to see the relationship of each variable. Statistical tests used Kendall's rank correlation and Spearman's rank correlation to see further interrelationships of significance between groups. The correlation value W = 0.58 with chi-square = 34.480 and p-value = 0.00000016 (p-value <0.01) which was statistically significant. Conclusion: The results showed significant relationship between malocclusion, bruxism, cliking sound and hypertonus of masseter muscle in autism spectrum disorders. However, there was no association between malocclusion with bruxism, malocclusion with clicking, malocclusion with hypertonus of masseter and bruxism with clicking. There was an association between bruxism and hypertonus of masseter.